Demarcated redness associated with increased vascular density/size: a useful marker of flat-type dysplasia in patients with ulcerative colitis - Ikebata, Akiyoshi; Shimoda, Masayuki; Okabayashi, Koji; Uraoka, Toshio; Maehata, Tadateru; Sugimoto, Shinya; Mutaguchi, Makoto; Naganuma, Makoto; Kameyama, Kaori; Yahagi, Naohisa; Kanai, Takanori; Kitagawa, Yuko; Kanai, Yae; Iwao, Yasushi (Endoscopy International Open, 2021)
Background and study aims Recent advances in endoscopic equipment and diagnostic techniques have improved the detection of dysplasia in the inflamed mucosa of patients with ulcerative colitis (UC). However, it remains difficult to endoscopically identify flat-type dysplasia which has been formerly recognized as invisible dysplasia.Patients and methods In this retrospective, single-center study, we endoscopically identified 10 cases of flat-type-predominant dysplasia by targeted biopsy among 38 intramucosal dysplasia lesions from patients with UC who underwent surgical or endoscopic resection from 2007 to 2017. Their endoscopic and histological features were examined, including color changes, intramucosal vascular density/size, and vascular endothelial growth factor (VEGF) expression.Results All flat-type-predominant dysplasias were endoscopically recognized as demarcated red-colored areas and histologically diagnosed as low- (LGDs) or high-grade dysplasias (HGDs). Immunohistochemical examination using resected specimens revealed that flat-type dysplasia was characterized by significantly increased CD34-positive vascular density (LGDs, 1.7-fold, P < 0.01; HGDs, 2.2-fold, P < 0.01) and size (LGDs, 1.03-fold, P < 0.01; HGDs, 1.11-fold, P < 0.01) in the mucosa, compared to adjacent non-neoplastic areas. Increased numbers of vessels were observed at the base of the mucosa in LGDs, whereas HGDs contained increased/enlarged vessels throughout the mucosa. Moreover, VEGF expression was elevated in all dysplastic epithelia.Conclusions Demarcated red-colored areas, histologically characterized by an increased vascular density/size in the mucosa, are an endoscopic sign of formerly invisible flat-type dysplasia in patients with UC and should be considered for targeted biopsy. Prospective studies focusing on the mucosal color change for their early detection would be desirable in the future.